Optimization Design and Simulation of Bottle Gripper based on MATLAB and ADAMS - Wang Chaoyang; Geng Chunming (Jixie chuandong)
A self-locking clamping device is designed,and the Solid Works software is used to carry out the 3D modeling of this gripper. The mathematical model of the offset slider rocker mechanism is established.Then,by using the software of MATLAB,the structure of the gripper is optimized,so that its stroke of the slider is minimum,while the maximum open angle is reasonable and its structure without interference. Finally,by using the ADAMS software,the dynamics simulation is carried out,and the result of calculation and verification meets the requirements.